2005
DOI: 10.1063/1.2140470
|View full text |Cite
|
Sign up to set email alerts
|

Device structure for electronic transport through individual molecules using nanoelectrodes

Abstract: Conformations and charge transport characteristics of biphenyldithiol self-assembled-monolayer molecular electronic devices: A multiscale computational study Theoretical investigation on electron transport through an organic molecule: Effect of the contact structure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 21 publications
5
35
0
Order By: Relevance
“…[83] While more recently, it has been well utilized to fabricate nanogap electrodes for nanodevices. [84][85][86][87][88][89] The passage of a large density current or application of a large direct current (dc) voltage to the thin metal wire predefined by electron-beam lithography would cause the electromigration of metal atoms and eventual breakage of the nanowire. This process can yield a stable electrode separation of 1 nm with high efficiency [84] and it can be monitored in real time by observing the current-voltage characteristics until only a tunneling signal is present.…”
Section: Electromigration For Nanogap Electrodesmentioning
confidence: 99%
“…[83] While more recently, it has been well utilized to fabricate nanogap electrodes for nanodevices. [84][85][86][87][88][89] The passage of a large density current or application of a large direct current (dc) voltage to the thin metal wire predefined by electron-beam lithography would cause the electromigration of metal atoms and eventual breakage of the nanowire. This process can yield a stable electrode separation of 1 nm with high efficiency [84] and it can be monitored in real time by observing the current-voltage characteristics until only a tunneling signal is present.…”
Section: Electromigration For Nanogap Electrodesmentioning
confidence: 99%
“…Depending on the experimental setup, measured conductances vary between 10 −4 G 0 and 10 −1 G 0 [41,42,43,44,45], while the calculated values typically lie in the range (0.05 − 0.4) G 0 [3,13,16,17,18,46,47,48]. In general it has been found that the transmission function is strongly dependent on the bonding site of the S atom [18,47], while variations in the Au-S bond length only affects the transmission function weakly [46].…”
Section: Benzene-14-dithiol (Bdt) Between Au(111) Surfacesmentioning
confidence: 99%
“…However, the assembly of molecular structures in junctions for electric and magnetic manipulation is a challenging task. [1][2][3][4] Carbon nanotubes (CNTs) are particularly promising as building blocks of new devices for nanoelectronics, [5][6][7][8] which exhibit interesting spin properties [9][10][11][12] and can be useful for quantum information processing. 13,14 Fundamental aspects of single-molecule devices require an understanding of strong perturbations by environmental effects, for example, the interaction with contacts or neighboring molecules.…”
mentioning
confidence: 99%